The Influence of Science, Technology, and Society Learning Model on Higher Order Thinking Skills in Grade IV Science Lessons - Sherlin Norma Azzahra; Apri Kartika H.S; Dian Nur Antika Eky (International Journal of Educational and Life Sciences, 2024)
This study was conducted to examine the effect of the Science, Technology, and Society (STS) learning model on Higher Order Thinking Skills in science lessons in grade IV. This study uses a quantitative approach with a type of quasi experimental research that uses a pre-test and post-test research design. The sampling technique used a probability sampling technique. The sample in this study was 17 students from grade IV at SDN 02 Nambangan Kidul Madiun. The data collection technique is using a test. The results of the data analysis show a significant difference upward as indicated by the mean of the two tests that have been conducted. The average or mean produced in the pre-test is 81.76 and the mean in the post-test is 91.18. The conclusion is Science, Technology and Society learning model influences on the Higher Order Thinking Skills (HOTS) of Science Lessons in Grade IV.